2003
DOI: 10.1002/jmv.10415
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human herpesvirus 6 with human CD34 positive cells

Abstract: We reported previously that human herpesvirus 6 (HHV-6) suppresses hematopoietic colony formation of erythroid (BFU-E), granulocyte/macrophage (CFU-GM), and megakaryocyte (CFU-Meg) lineages in vitro. Here we describe the interaction between HHV-6 and human CD34+ cells, which are a major source of hematopoietic progenitor cells. CD34+ cells were immunomagnetically isolated from cord blood mononuclear cells using anti-CD34+ antibodies coated onto either Dynabeads trade mark or MACS beads. The CD34+ population se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Studies of human CMV, a ␤-herpesvirus that is 67% homologous to HHV-6 at the protein level (Dominguez et al, 1999), as well as murine CMV have demonstrated an inhibition of the G 1 /S phase transition in several distinct cell systems (Wiebusch and Hagemeier, 1999;Kosugi et al, 2000;Flemington, 2001;Castillo and Kowalik, 2002). HHV-6 has been demonstrated to be able to infect and arrest human bone marrow progenitor cells in vitro (Luppi et al, 1999;Isomura et al, 2003) and in vivo (Wilborn et al, 1994;Rosenfeld et al, 1995;Secchiero et al, 1995) and to suppress proliferative responses to antigens and mitogens (Burd and Carrigan, 1993;Horvat et al, 1993;Carrigan and Knox, 1995). Our studies now extend the importance of viral-mediated cell cycle arrest to relevant neural precursor cells and show that this arrest is coupled with alterations in their differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of human CMV, a ␤-herpesvirus that is 67% homologous to HHV-6 at the protein level (Dominguez et al, 1999), as well as murine CMV have demonstrated an inhibition of the G 1 /S phase transition in several distinct cell systems (Wiebusch and Hagemeier, 1999;Kosugi et al, 2000;Flemington, 2001;Castillo and Kowalik, 2002). HHV-6 has been demonstrated to be able to infect and arrest human bone marrow progenitor cells in vitro (Luppi et al, 1999;Isomura et al, 2003) and in vivo (Wilborn et al, 1994;Rosenfeld et al, 1995;Secchiero et al, 1995) and to suppress proliferative responses to antigens and mitogens (Burd and Carrigan, 1993;Horvat et al, 1993;Carrigan and Knox, 1995). Our studies now extend the importance of viral-mediated cell cycle arrest to relevant neural precursor cells and show that this arrest is coupled with alterations in their differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…HHV-6 has been suspected of causing vascular endothelial damage in BMT recipients, a process that may lead to thrombotic microangiopathy, which is a major complication of BMT (273,389). Lastly, HHV-6 infection has been associated with bone marrow suppression (52,113), an observation that is supported by in vitro data on the suppressive effects of HHV-6 on proliferation of stromal cells of granulocyte/macrophage, erythroid, or megakaryocyte lineages (48,(187)(188)(189)212). A recent retrospective study by Boutolleau et al (42) in 78 stem cell transplant recipients found a correlation between HHV-6 viral load in PBMCs and delayed neutrophil engraftment, severe graft-versus-host disease, and classical HHV-6 manifestations, such as fever and rash.…”
Section: Clinical Manifestations Of Hhv-6 Infectionmentioning
confidence: 97%
“…After re-suspension, cells were counted. Semi-solid cultures of granulocyte/monocyte colony-forming units (CFU-GM), erythroid burst-forming units (BFU-E), and megakaryocyte CFUs (CFU-Meg) were established according to the published literature [20].…”
Section: Methodsmentioning
confidence: 99%